Impacts of wind farms on swans and geese: a review - Rees, Eileen C (Wildfowl, 2012)
This review considers data published on the effects of offshore and onshore windfarms on swans and geese and finds that the information available is patchy. Of 72 swans or geese reported as collision victims at 46 wind farms, most (39 birds) were reported at 23 wind farms in Germany where such data are collated. Post-construction monitoring was undertaken for ≤ 1 year at 67% of 33 sites, making it difficult to test for cumulative effects or annual variation in collision rates. Site use by the birds was measured at only nine of 46 wind farms where collisions by swans and geese were monitored or recorded. Displacement distances of feeding birds at wintering sites ranged from 100–600 m, but preliminary evidence suggested that large-scale displacement also occurs, with fewer swans and geese returning to areas after wind farms were installed. Eight studies of flight behaviour all reported changes in flight-lines for swans or geese initially seen heading towards the turbines, at distances ranging from a few hundred metres to 5 km; 50–100% of individuals/groups avoided entering the area between turbines, but in some cases the sample sizes were small. Key knowledge gaps remain, including whether wind farm installation has a consistently negative effect on the number of birds returning to a wintering area; whether flight avoidance behaviour varies with weather conditions, wind farm size, habituation and the alignment of the turbines; provision of robust avoidance rate measures; and the extent to which serial wind farm development has a cumulative impact on specific swan and goose populations. It is therefore recommended that: 1) post-construction monitoring and dissemination of results be undertaken routinely, 2) the extent to which wind farms cause larger-scale displacement of birds from traditional wintering areas be assessed more rigorously, 3) further detailed studies of flight-lines in the vicinity of wind farms should be undertaken, both during migration and for birds commuting between feeding areas and the roost, to provide a more rigorous assessment of collision and avoidance rates for inclusion in collision risk models, and 4) the combination of collision mortality and habitat loss at all wind farms in the species’ range be analysed in determining whether they have a significant effect on the population.